Never Idle: The Animated Screensaver and the Culture of Always-On Computing. - FORCIER, KAITLIN CLIFTON (Afterimage, 2021)
The article focuses on an exhibition at the Iris & B. Gerald Cantor Art Center at Stanford University that present a suite of moving-image works created in a form not often seen in the context of the art gallery that is the animated screensaver. Topics include considered that screensaver is unique as a genre of moving image in that and it does not have a discrete length, but rather will continue for an indefinite period of time.